La revue Actes : le droit saisi par le regard critique dans le sillage de 68 - Liora Israël (Revue d’Histoire des Sciences Humaines)
The history of the journal Actes: Cahiers d’action juridique leads to reconsider how critical approaches of law were reshaped after May 68 events. The journal was initially founded by politically oriented lawyers, and was built upon the conciliation of critical legal theory and new forms of political lawyering typical of the period. Progressively, in relation with the diversification of its members, the journal developed an orientation toward social sciences and humanities, notably under the intellectual influence of Michel Foucault.